Perancangan Aplikasi Kinerja Karyawan Berbasis Android Di Umkm Handmade Tas Fashion - Fiolitta , Anggi; Dijaya, Rohman (Universitas Nusantara PGRI Kediri, 2022)
faaz collection is a company. handmade bag A company that still collecting data company. manually Resulting in less than accurate. dataIn this research writer provide solutions to design an application based on android by means of taking data manual is a collection to faaz diinputkan employee performance based on the application. androidThis study using. quantitative research methodology Design application employee performance based on android this in a waterfall. System development life cycle is a system that was developed to include all data needed to form, create. information systemIn making the android application was supported by emulator or device smartphone asus zenfone zoom s as testing an application. emulatorOn the research and test results have been made which is to simplify the application of the company in the monitoring, employee performance helped with rekapan, absentee manage easily, absentee have the charts order so that the owners can monitor the development of the company through charts.